2023
DOI: 10.18087/cardio.2023.4.n2403
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for use of Vericiguat in HFrEF: Implications of VICTORIA Trial Results. Advisory Board Summary

Abstract: In September 2021, an online meeting of the Council of Experts was held. The proposed focus of discussion was publishing the results of an international prospective, randomized, double-blind, placebo-controlled study VICTORIA. The objective of the VICTORIA study was evaluation of the efficacy and safety of supplementing a standard therapy with vericiguat at a target dose of 10 mg twice a day as compared to placebo for prevention of cardiovascular death and hospitalization for heart failure (HF) in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Moreover, it also improved heart function, decreasing fibrosis and promoting diuresis [26]. In the VICTORIA trial, vericiguat demonstrated its safety in heart failure patients, reducing cardiovascular death or heart failure hospitalization [27,28]. Vericiguat's vasodilatory effects can help enhance blood flow to skeletal muscle, potentially improving its function and reducing symptoms such as exercise intolerance or sarcopenia [29].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it also improved heart function, decreasing fibrosis and promoting diuresis [26]. In the VICTORIA trial, vericiguat demonstrated its safety in heart failure patients, reducing cardiovascular death or heart failure hospitalization [27,28]. Vericiguat's vasodilatory effects can help enhance blood flow to skeletal muscle, potentially improving its function and reducing symptoms such as exercise intolerance or sarcopenia [29].…”
Section: Introductionmentioning
confidence: 99%